Analysis of Income Level and Shifts in Community Work Types during the Covid-19 Pandemic in Kanonang Satu and Kanonang Dua Villages - Fonny Rewah,; Ellen Eva Poli,; Erick Lobja, (Technium Social Sciences Journal, 2023)
This study seeks to provide an overview of income levels and shifts in the type of community work during the COVID-19 pandemic in Kanonang Satu and Kanonang Dua Villages. The results showed that: (1) The Covid-19 pandemic has affected the economic life patterns of the people of Kanonang Satu and Kanonang Dua including income received, expenses for daily living, employment, and spending habits dominated by buying groceries for daily life, (2) The impact of this pandemic is not only felt by those who live in urban areas but also those who live in rural areas such as in Kanonang Satu and Kanonang Dua.